2010
DOI: 10.1002/mus.21758
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of coenzyme Q10 in mitochondrial disorders

Abstract: Case reports and open-label studies suggest that coenzyme Q(10) (CoQ(10)) treatment may have beneficial effects in mitochondrial disease patients; however, controlled trials are warranted to clinically prove its effectiveness. Thirty patients with mitochondrial cytopathy received 1200 mg/day CoQ(10) for 60 days in a randomized, double-blind, cross-over trial. Blood lactate, urinary markers of oxidative stress, body composition, activities of daily living, quality of life, forearm handgrip strength and oxygen d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 63 publications
1
81
0
1
Order By: Relevance
“…A trial of CoQ 10 in adults with mitochondrial disorders was competed at McMaster University [25]. This was a randomized, double-blind, placebo-controlled study to determine the effects on exercise tolerance and capacity ( Table 1).…”
Section: Coq 10 and Idebenonementioning
confidence: 99%
“…A trial of CoQ 10 in adults with mitochondrial disorders was competed at McMaster University [25]. This was a randomized, double-blind, placebo-controlled study to determine the effects on exercise tolerance and capacity ( Table 1).…”
Section: Coq 10 and Idebenonementioning
confidence: 99%
“…Vitamins, minerals, and other metabolites supplementation may be a target Therapies for treatment of mitochondrial dysfunction and fatigue since they are necessary cofactors for the synthesis and function of mitochondrial enzymes and other compounds that support mitochondrial function [30,38,68,80,81]. Nevertheless the treatment of mitochondrial dysfunction and chronic fatigue is still inadequate, and their role in the treatment of the majority of these patients remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…51 Coenzyme Q 10 therapy was also reported to correct pancreatic b-cell dysfunction in patients with mitochondrial encephalomyopathy and lactic acidosis and diabetes mellitus. 52 However, the most consistent finding appears to be at the biochemical level with a decrease in plasma/serum lactate and pyruvate levels being widely reported following exercise 48,51,53,54,55,56,57,58 . In contrast, some studies have shown no evidence of clinical or biochemical improvement in patients following CoQ 10 supplementation 59,60 .…”
Section: Treatment Of Mrc Disordersmentioning
confidence: 91%
“…63,65 Although a number of small studies and case reports have illustrated the potential benefits of CoQ 10 in the treatment of patients with MRC disorder, 25 few controlled clinical trials have been conducted to evaluate its effectiveness. The trials that have been undertaken to date generally included patients with MRC disorder having variable genotypes and clinical phenotypes making it difficult to draw any firm conclusions to the responsiveness of particular groups of patients to CoQ 10 therapy 21,48,66,67 . Although 2 trials demonstrated no benefit in any of the outcomes, 61 evidence of improvement in muscle strength 21 and a decrease in plasma lactate levels following exercise 48 was reported.…”
Section: Treatment Of Mrc Disordersmentioning
confidence: 99%